One Pulmonary Lesion, 2 Synchronous Malignancies - Masooma Aqeel MD; Nevin Uysal-Biggs MD; Timothy S. Fenske MD; Nagarjun Rao MD, FRCPath (SAGE Publishing, 2018)
Introduction . Mantle cell lymphoma (MCL) comprises approximately 3% to 10% of all non-Hodgkin lymphomas. Although there is an increased risk for secondary malignancies after treatment among non-Hodgkin lymphomas survivors, a synchronous diagnosis of primary lung cancer arising in conjunction with lymphoma at the same site has rarely been reported. We report an unusual case of primary lung adenocarcinoma with coexistent MCL within the same lung lesion. Case Presentation . A 55-year-old female with newly diagnosed stage IV-B MCL was referred for workup of a right upper lobe cavitary lesion detected during lymphoma staging. A whole-body positron-emission tomography-computed tomography scan revealed diffuse adenopathy but also identified a cavitary right upper lobe lesion atypical for lymphoma. Bronchoscopy was unremarkable with cytology (on lavage) negative for malignancy. At 2 months, a computed tomography scan of the chest showed a persistent lesion. A video-assisted thoracoscopic wedge resection was performed. Histopathological examination revealed a lepidic predominant, well-differentiated adenocarcinoma (stage T1a) and foci of lymphoid infiltrate within and adjacent to the adenocarcinoma consistent with lung involvement by MCL. Discussion . Synchronous presentation of primary lung adenocarcinoma and lymphoma at a single site is exceedingly rare. Nonresolving pulmonary lesions with features atypical for lymphoma should be viewed with caution and worked up comprehensively to rule out occult second malignancies, in order to guide a prompt diagnosis and appropriate treatment.